Adaptations to sprinting and jumping after training with a resistance harness in track athletes - Clark, M.; Jensen, R. L.; Clarke, S. B.; Meidinger, R. L. (ISBS Proceedings Archive (Michigan), 2017)
The SpeedMaker resistive sprint device is claimed to elicit post-activation potentiation, improve knee height and upper leg drive to improve sprint performance. There was a total of 9 participants in the present study. The participants were tested on two days for changes in knee and hip angles, sprint times and changes in muscular activation. The present study found no presence of post-activation potentiation no evidence of changes improved knee height or upper leg drive from the SpeedMaker device. The purpose of the current study was to assess the claims that the SpeedMaker device improves sprint performance. The present study tested 10 female track and field and lacrosse athletes on the effects of this device. The findings of the present study is that the SpeedMaker device may decrease knee angle.